Triglyceride glucose-body mass index is associated with diabetic kidney disease in type 2 diabetes mellitus patients without non-alcoholic fatty liver disease - Chu, Yafen; Yao, Hongping; Lu, Ni; Chang, Yu; Wang, Jumei; Xu, Linlin; Song, Bing; Feng, Songtao; Zhang, Hui (Frontiers in Nutrition, 2025)
AimThe triglyceride glucose-body mass index (TyG-BMI) is correlated not only to the onset of diabetic kidney disease (DKD) associated with nutrition (including glucose and triglyceride) metabolism but also incorporates body mass index (BMI), potentially serving as an indicator of non-alcoholic fatty liver disease (NAFLD). But, the links between TyG-BMI and DKD in individuals with and without NAFLD remains further exploration. Therefore, this present research aims to investigate the relationship between TyG-BMI and DKD in these patient groups and to evaluate its diagnostic value for DKD.MethodsA total of 425 individuals diagnosed with type 2 diabetes mellitus (T2DM) were categorized into the DKD group or the Control group. Clinical indicators were compared in these two groups, and the relationships between TyG-BMI and either the estimated glomerular filtration rate (eGFR) or the urinary albumin-to-creatinine ratio (UACR) were examined. Risk factors for DKD were examined, and the diagnostic value of TyG-BMI was assessed in patients without and with NAFLD.ResultsCompared to 288 participants without DKD, 137 individuals with DKD exhibited higher TyG-BMI levels. In all individuals with T2DM, a higher TyG-BMI was recognized as a contributing factor to the development of DKD. Notably, this association was observed in patients without NAFLD, while no such link was established in those diagnosed with NAFLD. For T2DM patients lacking NAFLD, the TyG-BMI threshold of 49.2415 demonstrated a sensitivity of 91.3% and a specificity of 70.1%.ConclusionIncreased TyG-BMI values are associated with a higher risk of DKD and could act as potential indicators of DKD in individuals with T2DM.